2019
DOI: 10.2147/ijgm.s213535
|View full text |Cite
|
Sign up to set email alerts
|

<p>The expression of microRNA 146a in patients with ischemic stroke: an observational study</p>

Abstract: Aim We conducted the present prospective study to assess the level of microRNA (miRNA) 146a in patients with ischemic stroke and its correlation with patients’ characteristics. Methods We conducted an observational study that included adult patients (≥18 years old) who presented within 24 hrs after the onset of the symptoms of acute ischemic stroke. In addition, age- and sex-matched healthy volunteers were included as control group. The primary outcome in the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…No signi cant difference was found in the relative expression of miRNA-146a between T1 and T2 groups and the control group, which was inconsistent with the conclusion of Du [18] and Hend's study [19], who found that the expression level of miRNA-146a in the early stage (within 24 hours) of AIS was signi cantly lower than that in the control group. The reason might be different in the onset time and probably the limited number of cases included.…”
Section: Discussioncontrasting
confidence: 79%
“…No signi cant difference was found in the relative expression of miRNA-146a between T1 and T2 groups and the control group, which was inconsistent with the conclusion of Du [18] and Hend's study [19], who found that the expression level of miRNA-146a in the early stage (within 24 hours) of AIS was signi cantly lower than that in the control group. The reason might be different in the onset time and probably the limited number of cases included.…”
Section: Discussioncontrasting
confidence: 79%
“…In another study, the expression of miRNA-146a was found to be significantly decreased in patients with ischemic stroke. The expression of miRNA-146a was correlated with the severity of ischemic stroke and showed a significant decrease in patients with coma compared to healthy controls [ 171 ].…”
Section: Participation Of Mirna-146a In the Development Of Ischemic S...mentioning
confidence: 99%
“…NIHSS was used as a short-term prognostic scale within 24, 48, and 72 h after stroke onset in 43 studies, and four studies assessed the long-term prognosis of IS patients with the NIHSS score at 7 days [62,84] and 3 months [70,88]. GOS score was measured in two studies at 30 days [49,59], whereas in one study physical outcomes within 24 h were evaluated by GCS [48]. mRS and BI were used to evaluate long-term prognosis.…”
Section: Prognostic Tools and Prediction Of Physical Recovery In Is P...mentioning
confidence: 99%